Protective Role of Collectin 11 in a Mouse Model of Rheumatoid Arthritis. Issue 8 (7th July 2021) - Wang, Na; Wu, Weiju; Qiang, Cui; Ma, Ning; Wu, Kunyi; Liu, Dan; Wang, Jia‐Xing; Yang, Xiao; Xue, Li; Diao, Teng‐Yue; Liu, Jia‐Yu; Li, Ang; et al.
Abstract : Objective: Collectin 11 (CL‐11) is a soluble C‐type lectin, a mediator of innate immunity. Its role in autoimmune disorders is unknown. We undertook this study to determine the role of CL‐11 in a mouse model of rheumatoid arthritis (RA). Methods: A murine collagen‐induced arthritis (CIA) model was used and combined two approaches, including gene deletion of Colec11 and treatment with recombinant CL‐11 (rCL‐11). Joint inflammation and tissue destruction, circulating levels of inflammatory cytokines, and adaptive immune responses were assessed in mice with CIA. Splenic CD11c+ cells were used to examine the influence of CL‐11 on antigen‐presenting cell (APC) function. Serum CL‐11 levels in RA patients were also examined. Results: Colec11 −/− mice developed more severe arthritis than wild‐type mice, as determined by disease incidence, clinical arthritis scores, and histopathology ( P < 0.05). Disease severity was associated with significantly enhanced APC activation, Th1/Th17 responses, pathogenic IgG2a production and joint inflammation, as well as elevated circulating levels of inflammatory cytokines. In vitro analysis of CD11c+ cells revealed that CL‐11 is critical for suppression of APC activation and function. Pharmacologic treatment of mice with rCL‐11 reduced the severity of CIA in mice. Analysis of human blood samples revealed that serum CL‐11 levels were lower in RA patients (n = 51) compared to healthy controls (n = 53). Reduction in serum CL‐11 was inversely associated with the Disease Activity Score in 28 joints, erythrocyte sedimentation rate, and C‐reactive protein level ( P < 0.05). Conclusion: Our findings demonstrate a novel role of CL‐11 in protection against RA, suggesting that the underlying mechanism involves suppression of APC activation and subsequent T cell responses.